Perlindungan Hukum Terhadap Pasien Dalam Sengketa Medis Aris Priyadi - Aris Priyadi (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2020)
Â Protection for patients in addition to being regulated in Law Number 29 of 2004 concerning Medical Practices is also regulated in the Civil Code specifically regulating defaults and acts against the law. In the event of a dispute between the doctor and the patient, where the patient feels disadvantaged over the services that have been carried out by the doctor/ hospital, almost all of which can not be said at all, are related to compensation issues due to acts against the law. Losses suffered by patients can be in the form of material losses and immaterial losses. Claims for compensation due to acts against the law as stipulated in Article 1365 of the Civil Code can be in the form of material compensation or immaterial compensation or can also both. Based on the provisions of Article 1365 of the Civil Code which stipulates that: Every act that violates the law that brings harm to others requires that the person who wrongfully issued the loss compensates the loss. Article 1365 of the Civil Code uses the principle/ concept of accountability based on mistakes. These provisions are certainly not favorable for the victim (patient) because they have to prove the existence of the error. The provision of proof is regulated in Article 163 HIR jo Article 1865 of the Civil Code regarding the burden of proof. The contents of this article are those who claim a right, or to assert their own rights or deny the rights of others, referring to an event, are required to prove their claim or event.Keywords: Legal protection, patients, compensation.Â Abstrak. Perlindungan terhadap pasien selain diatur dalam Undang-Undang Nomor 29 tahun 2004 tentang Praktik Kedokteran diatur pula dalam KUH Perdata khususnya yang mengatur tentang wanprestasi dan perbuatan melawan hukum. Apabila terjadi sengketa antara dokter dengan pasien, dimana pasien merasa dirugikan atas pelayanan yang telah dilakukan oleh dokter/rumah sakit, hampir semua kalau tidak dapat dikatakan semuanya, adalah menyangkut masalah ganti rugi akibat perbuatan melawan hukum. Kerugian yang diderita pasien dapat berupa kerugian materiil dan kerugian immateriil. Tuntutan ganti rugi karena perbuatan melawan hukum sebagimana diatur dalam Pasal 1365 KUH Perdata dapat berupa ganti rugi materiil atau ganti rugi immateriil atau dapat juga keduanya. Berdasarkan ketentuan Pasal 1365 KUH Perdata yang menentukan bahwa: Tiap perbuatan melanggar hukum yang membawa kerugian kepada orang lain mewajibkan orang yangkarena salahnya menerbitkan kerugian itu, mengganti kerugian tersebut. Pasal 1365 KUH Perdata menggunakan prinsip/konsep tanggung gugat atas dasar kesalahan. Ketentuan tersebut tentunya kurang menguntungkan bagi korban (pasien) karena harus membuktikan adanya kesalahan tersebut. Adapun ketentuan pembuktian diatur dalam Pasal 163 HIR jo Pasal 1865 KUH Perdata tentang beban pembuktian. Isi dari pasal tersebut adalah siapapun yang menuntut suatu hak,atau guna meneguhkan haknya sendiri ataupun membantah hak orang lain, menunjuk pada suatu peristiwa, diharuskan membuktikan tuntutan haknya atau peristiwa tersebut.Kata kunci : Perlindungan hukum, pasien, ganti rugi.